Fascism and the forced italianization of names and toponyms on the “eastern border” - Nencioni, Chiara (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
The essay deals with the violent denationalization process of the Slavic minorities in the territories of Venezia Giulia annexed to Italy after the First World War. Liberal Italy already adopted policy that tend to assimilate the Slavic populations; but fascism adds a strong charge of violence feeling an evident sense of ethnic superiority. The fire of the Narodni Dom is the announcement of the forced denationalization policy implemented by the so-called border fascism. The fascist state implemented the forced Italianization of names and toponyms and imposed the Italian language in every aspect of public life: courts, schools, churches. The essay aims to analyze the role that the authoritarian change of names, surnames and toponyms had in the process of forced assimilation into the Italian state of the eastern territories acquired after World War I. We use information from essays, literature, testimonies and legal texts.